PENGARUH MOTIVASI KERJA TERHADAP PELAKSANAAN FUNGSI MANAJEMEN KEUANGAN DALAM PENGELOLAAN PENDAPATAN NEGARA BUKAN PAJAK (PNBP) DAN DAMPAKNYA TERHADAP PELAKSANAAN AKUNTABILITAS KEUANGAN PADA UNIVERSITAS SYIAH KUALA - Alfi Syahril Fuadi Jaya (Program Magister Akuntansi Unsyiah, 2011)
This study is done at the Syiah Kuala University which aim to examine the influence of job motivation and the implementation of financial management to the implementation of financial accountability either simultaneously or partially.This research used census method. Respondents of this research are finance organizer at Syiah Kuala University. The objective of this research is to be able to seek the influence between job motivation, the implementation of financial management and the implementation of financial accountability. This research use 18 populations peoples. The data used are primary data by using questionnaires to the respondents directly. Technics of data analysis used is path analysis. Results of this research indicate that by simultaneously or partially job motivation and the implementation of financial management have influence to the implementation of financial accountability. Job motivation has influence to the implementation of financial management Keyword: job motivation, the implementation of financial management and the implementation of financial accountability